Foldable and portable cupboard - Mohd Rahmat, Ahmad Suhaimin (2011)
Cupboard functions as storage to store clothes and make clothes arrangement systematic and tidy besides protecting our clothes .Cupboard by itself have faced evolution from first time it had build until now. We can see there are so many differences between the older cupboard and the new one. Differences in context of design, material they used, and the way to assemble it. However, there are obviously two types of cupboard which are permanent assemble and foldable. The foldable cupboard nowadays is designed using fabric as the structure cover and aluminium and PVC as the frame of cupboard. Yet, it is not stable, not durable and has short life spend. Due to this problem, a new portable and foldable cupboard is developed. There are four concepts, it was suggested those concept 4 is decided to be the best concept. The installation process of the cupboard is discussed into detail between pilot designed and actual product. Later, this cupboard is modeled using SolidWorks software. Further, the scale of 1:4 is used to fabricate the pilot model. After the fabrication process, it is founded that the designed modeling of foldable is specified to fold the cupboard is totally different compared to pilot model due to lack of resources. Still, folding design for both modeling and pilot modeling can be used as actual folding method because the material selection which is PVC for structure cover are high in strength and have moisture resistant compared to current product. The processes to fabricate this cupboard used cutting, joining, and finishing.